The Effect of Hydrocarbonoclastic Bacteria Bioaugmentation (Bacillus sp. & Alcaligenes sp.) toward Soil pH - Marcloryne Agnesia; Yuni Ahda (Serambi Biologi, 2020)
The used lubricant oil is one of the petroleum derivates wich contains an alkane group with 17-22 carbon atoms. In general, petroleum waste has not been managed optimally. One of the effective methods of combating petroleum waste is by involving hydrocarbonoclastic bacteria. The purpose of this research is to determine the effect of hydrocarbonoclastic bacteria bioaugmentation on soil pH values. This research was conducted in June until December 2018. This study used a single indigenous bacterium and consortium (Bacillus sp. and Alcaligenes sp.) which was isolated from contaminated soil by Ahda and Fitri (2016). pH measurements were carried out on the 1st 2nd 3th, 4th, 5th and 6th week. The results showed that the amount of bioaugmentation affected the soil pH value in the third week, and the type of bacteria began to affect the soil pH in the sixth week. The results of this study indicate that bioaugmentation affects the pH value of used oil contaminated soil.